Dynamic diffusion of hybrid rice varieties and the effect on rice production: evidence from China - Wang, Qiaoyu; Bin, Bing; Wang, Huaiyu (Frontiers in Sustainable Food Systems, 2023)
The improvement of crop productivity is the key factor to satisfy the increasing food demand with limited water and land resources under climate change. The adoption of modern rice varieties is of primary importance to improve and stabilize the world’s rice production, and the wide adoption of hybrid rice varieties in China is a successful example showing the role of agricultural technology in terms of food security. However, the dynamic diffusion of hybrid rice varieties and the effect on rice production remain to be studied. Based on the data of hybrid rice adoption at provincial level from 1984-2011, the study identifies the distribution of hybrid rice varieties across the rice producing areas of China. We applied OLS and GTWR models to investigate the spatial and temporal effects of hybrid rice adoption at national and provincial level. Overall, the effects of hybrid rice adoption on rice production have decreased over time. Also, the results show a possible spillover and crowding effect of hybrid rice adoption across provinces. Particularly, the development of hybrid rice varieties in Hunan province have had a significant influence on the changes of rice yield and distribution of rice area in other areas. The study can be a reference for developing countries to understand the dynamic distribution of high-yield rice variety adoption in relation to food security, and for further designing appropriate agricultural extension strategies. However, further study is needed to identify the determinants affecting the changes of rice farming in the complex environment associated with the ecological system.